Bothynus entellus (LePeletier & Serville) (Coleoptera: Scarabaeidae: Dynastinae) species group: taxonomic revision and description of two new species - Duarte, Paulo R.m.; Grossi, Paschoal C. (Zootaxa, 2020)
The Bothynus entellus (LePeletier & Serville) (Coleoptera: Scarabaeidae: Dynastinae: Pentodontini) species group is reviewed with redescriptions, diagnoses, illustrations, and separate identification keys to males and females. Distribution maps for all species in this species group are presented for the first time. Furthermore, two new species, Bothynus araya Duarte & Grossi new species and Bothynus condacki Duarte & Grossi new species, are described.